(untitled) (International Journal of Environmental Sciences, 2025)
AIM: To comparatively evaluate the clinical performance, survival, and complications of screw-retained versus cement-retained implant-supported prostheses MATERIALS AND METHODS: This prospective, randomized clinical trial was designed to compare screw-retained and cement-retained implant prostheses. Ethical approval was obtained prior to commencement, and informed consent was taken from all participants. Adults between 20 and 65 years of age who required single implant-supported crowns, were systemically healthy, and had adequate bone volume for implant placement were included. Patients with uncontrolled systemic diseases, history of radiotherapy, smoking of more than ten cigarettes per day, pregnancy, parafunctional habits, or previous implant failures were excluded. A total of 50 implants were placed and randomly allocated into two equal groups, with 25 implants each for screw-retained and cement-retained prostheses. Randomization was carried out using computer-generated numbers in sealed opaque envelopes. RESULTS: In our study, 50 patients were evaluated, equally divided into screw-retained and cement-retained groups with comparable baseline characteristics. At the 12-month follow-up, both groups demonstrated 100% implant and prosthesis survival with high patient satisfaction. Clinical outcomes such as probing depth, plaque index, gingival index, and peri-implant health showed no significant differences, except for marginal bone loss which was significantly lower in the screw-retained group. Prosthetic complications were minimal, with screw loosening seen only in screw-retained prostheses and loss of retention observed only in cement-retained restorations. Overall, both retention types performed successfully, though screw-retained prostheses exhibited slightly more favorable bone preservation. CONCLUSION: Both screw-retained and cement-retained implant prostheses show comparable success, with the final choice best guided by individual patient needs and clinical considerations.